Development of a Time Domain Reflectometer Application Using Matlab/Simulink for Detecting Faults in Electrical Cables - Moldovan, Ana-Maria; Buzdugan, Mircea Ion (International Conference on Applied and Theoretical Electricity (Online), 2024)
The paper presents an application of a time domain reflectometer, using a Simulink model and Matlab App Designer intended to explore the importance of proper use of the real time domain reflectometer equipment. To highlight the usefulness of this application, the information presented in the paper is divided into four sections. The introductory section is devoted to the need to maintain the integrity of electrical cables in good condition. In the second section a time domain reflectometer equipment and its operating principle are described. The development of a friendly interactive interface of a time domain reflectometer model is detailed in the third section. Finally, in the last section is emphasized the use of the proposed application.